ANALISA PENILAIAN KINERJA KARYAWAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DI UD. MARIADI RANGKA - Rini Halila Nasution; Yetti Meuthia Hasibuan; Jumadi Suratman; Alda Febriansyah Chaniago; Suriandi Suriandi (Jurnal Simetri Rekayasa, 2020)
UD. Mariadi Rangka is a business engaged in furniture, precisely in the manufacture of sofa frames. For optimal productivity results, employees who have expertise and work discipline are needed. In this case the company UD. Mariadi Rangka has not implemented a Performance Appraisal system, therefore it is necessary to assess the performance of employees to assist the company in making decisions such as promotion of positions, giving bonuses, wage increases, and termination of work. The conclusion of the results of this study is that there are 5 weight criteria that will be used as a reference in employee performance assessment, namely attendance with a weight of 30, ethics with a weight of 15, time discipline with a weight of 20, work quality with a weight of 20, and quantity of results with a weight of 15. From the calculation of Sugeng are employees best in UD. Mariadi Rangka with a Preference value of 89,9.